Dicyanodistyrylbenzene based positional isomers: a comparative study of AIEE and stimuli responsive multicolour fluorescence switching. (22nd December 2021) - Ramya, N. K.; Femina, C.; Suresh, Suganya; Mohanakumari, Divya S.; Krishnan, Retheesh; Thomas, Reji
Abstract : Positional isomers of α-dicyanodistyrylbenzene core systems were synthesized and studied for the AIEE effect and stimuli responsive fluorescence colour switching. Abstract : This study reports a detailed analysis of fluorescence switching in a series of octyloxy substituted α-dicyanodistyrylbenzene positional isomers in combination with structures derived from single crystal X-ray diffraction. All the compounds in this report have shown aggregation induced enhanced emission (AIEE) in the solid-state in spite of very weak fluorescence in their solutions. The ortho isomer showed comparatively weak fluorescence in the crystalline phase which can be attributed to quenching due to the π–π stacking interactions, whereas the crystals on grinding resulted in a mechanochromic fluorescence blue shift with an enhanced quantum yield. The meta isomer showed a twofold enhancement in fluorescence quantum yield in the ground form without significant spectral shifts. The para isomer showed three distinct emissive solid phases that are interconvertible upon exposure to stimuli such as heat, pressure and solvent vapours. The analysis of powder X-ray diffractograms of different phases of the para isomer in correlation with the single crystal X-ray data of phase-1 (CSP1 ) has shown that the molecular packing and change in the planarity of the conjugated π-backbone lead to different levels of coupling and therefore different fluorescence emission. The molecules in CSP1 show a twist in the π-system with an angle of 61° with cyan emission whereas the second phase (CSP2 ) with green emission has a perfectly lamellar arrangement. Both CSP1 and CSP2 on grinding convert to a deep yellow emissive phase (CSP3 ) and the thermal annealing and treatment with solvent vapours resulted in the recovery to phases similar to CSP1 or CSP2 . The present study shows that in addition to the molecular packing, the planarity of the molecules and the strength of intermolecular interactions play a crucial role in the stimuli responsive nature of these compounds.